2018
DOI: 10.1096/fj.201701321rr
|View full text |Cite
|
Sign up to set email alerts
|

Fat storage‐inducing transmembrane protein 2 (FIT2) is less abundant in type 2 diabetes, and regulates triglyceride accumulation and insulin sensitivity in adipocytes

Abstract: Fat storage-inducing transmembrane protein 2 (FIT2) aids in partitioning of cellular triacylglycerol into lipid droplets. A genome-wide association study reported FITM2-R3H domain containing like-HNF4A locus to be associated with type 2 diabetes (T2DM) in East Asian populations. Mice with adipose tissue (AT)-specific FIT2 knockout exhibited lipodystrophic features, with reduced AT mass, insulin resistance, and greater inflammation in AT when fed a high-fat diet. The role of FIT2 in regulating human adipocyte f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…One of the main gene Diacylglycerol O-acyltransferases (DGAT2) is involved in triacylglycerol metabolism ( Bhatt-Wessel et al, 2018 ). While FITM2 (Fat Storage Inducing Transmembrane Protein 2) is a storage protein and its abundance is affected in type 2 diabetes ( Agrawal et al, 2019 ). The two isoforms PCK1 and 2 of phosphoenolpyruvate carboxy kinase are involved in the gluconeogenesis; these enzymes are dysregulated in the obesity and diabetes ( Beale et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…One of the main gene Diacylglycerol O-acyltransferases (DGAT2) is involved in triacylglycerol metabolism ( Bhatt-Wessel et al, 2018 ). While FITM2 (Fat Storage Inducing Transmembrane Protein 2) is a storage protein and its abundance is affected in type 2 diabetes ( Agrawal et al, 2019 ). The two isoforms PCK1 and 2 of phosphoenolpyruvate carboxy kinase are involved in the gluconeogenesis; these enzymes are dysregulated in the obesity and diabetes ( Beale et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mammals have two FIT proteins, FIT1 and FIT2. FIT2 has been confirmed to play an important role in LD formation [ 14 , 50 ]. Biochemical analyses confirmed that FIT2 directly and specifically binds to both TAG and its immediate precursor DAG, while purified FIT2 proteins have no intrinsic TAG biosynthetic activity.…”
Section: Nucleation Of Ldmentioning
confidence: 99%
“…Moreover, similar to seipin, other ER-located proteins involved in LD biogenesis such as fat storage-inducing FIT2, Atlastin, REEP1 and so on are also closely associated with human diseases. For example, FIT2 has been certified to play a key role in lipodystrophy [ 172 ], diabetes mellitus [ 173 , 174 ], and hepatocellular carcinoma [ 175 ], as well as doxorubicin-mediated cardiotoxicity [ 176 ], and the underlying mechanisms are also incompletely clear. Therefore, it is of great significance to study the precious mechanism of these proteins in diseases, and studies focusing on seipin are excellent examples of them.…”
Section: Conclusion and Perspectivementioning
confidence: 99%